PEMANFAATAN GLISERIN DARI RESIDU GLISERIN SEBAGAI PLASTICIZER UNTUK PEMBUATAN BIOPLASTIK DENGAN BAHAN BAKU PATI BONGGOL PISANG KEPOK - Azaria Robiana; M. Yashin Nahar; Hamidah Harahap (Talenta Publisher (Universitas Sumatera Utara), 2016)
Glycerin residue is waste oleochemical industry that still contain glycerin. To produce quality and maximum quantity of glycerin, then research the effect of pH acidification using phosphoric acid. Glycerin analysis includes the analysis of pH, Fatty Acid and Ester (FAE), and analysis of the levels of glycerin. The maximum yield obtained at pH acidification 2 is grading 91,60% glycerin and Fatty Acid and Ester (FAE) 3,63 meq/100 g. Glycerin obtained is used as a plasticizer in the manufacture of bioplastics. Manufacture of bioplastics using the method of pouring a solution with varying concentrations of starch banana weevil (5% w/v and 7% w/v), variations of the addition of glycerin (1 ml, 3 ml, 5 ml and 7 ml), and a variety of gelatinization temperature (60°C, 70°C, and 80°C). Analysis of bioplastics include FTIR testing, tensile strength that is supported by SEM analysis. The results obtained in the analysis of FTIR does not form a new cluster on bioplastics starch banana weevil, but only a shift in the recharge area only, it is due to the addition of O-H groups originating from water molecules that enter the polysaccharide through a mechanism gelatinitation that generates interaction hydrogen bonding strengthened. The maximum tensile strength of bioplastics produced at a concentration of starch 7% w/v, 1 ml glycerine and gelatinization temperature of 80°C is 3,430 MPa. While the tensile strength bioplastic decreased with increasing glycerin which can be shown from the results of SEM where there is a crack, indentations and lumps of starch insoluble.